2019
DOI: 10.1002/mnfr.201801417
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol‐Monolaurate‐Mediated Attenuation of Metabolic Syndrome is Associated with the Modulation of Gut Microbiota in High‐Fat‐Diet‐Fed Mice

Abstract: Scope: The gut microbiota plays an important role in the development of diet-induced obesity and metabolic syndrome. Glycerol monolaurate (GML), a widely consumed food emulsifier, is reported to promote metabolic disorder and gut microbiota dysbiosis in low-dose supplementation upon low-fat-diet feeding. However, little is known about whether GML produce the same effects in mice fed a high-fat diet (HFD). Methods and results: C57BL/6 mice are fed a HFD with or without GML supplementation (150, 300, and 450 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…3 However, controversially, some studies have also indicated that the prevention of obesity was not associated with the change in the F/B ratio. 34,35 Despite no signicant difference at the phylum level, a series of specic species at the genus level positively correlated with obesity and obesity-related physiological parameters were found. Unclassied_f__Lachnospiraceae and Allobaculum were enriched in the HFD-fed groups, whereas Blautia and Bidobacterium were markedly decreased.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3 However, controversially, some studies have also indicated that the prevention of obesity was not associated with the change in the F/B ratio. 34,35 Despite no signicant difference at the phylum level, a series of specic species at the genus level positively correlated with obesity and obesity-related physiological parameters were found. Unclassied_f__Lachnospiraceae and Allobaculum were enriched in the HFD-fed groups, whereas Blautia and Bidobacterium were markedly decreased.…”
Section: Discussionmentioning
confidence: 90%
“…37 Some studies have also proved that an increase in Lactobacillus could reduce intestinal endotoxin, alleviate metabolic syndrome, and suppress obesity-related inammation. 35,38 Therefore, the relatively better effects of CSPH on metabolic disorders might be through the synergism of Blautia and Lactobacillus. In line with the change in the gut microbiota composition, CSP supplementation also exhibited a better intestinal integrity than the HFD groups, and signicantly increased the expression of epithelial tight junction proteins ZO-1 and occludin to protect the intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…GML had the strongest antimicrobial capacity among the medium chain 1-monoglycerides (MGs) and possess a broad antibacterial spectrum, especially in suppressing the growth of gram-positive bacteria in vitro [11]. Dietary GML in the diet of mice significantly altered the composition, microbial metabolite and function of gut microbiota, which consequently affected the animal performance and nutrients utilization [41,42]. The present study revealed that the gut microbiota composition and function were altered by GML supplementation, but their relationship with laying performance and feed efficiency required further study.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota (GM) play an important role in the metabolic cycle, immune response regulation (Tian et al, 2019), gut barrier function (Gao et al, 2018), obesity (Zhao et al, 2019), and MetS, via influencing effector molecules such as short-chain fatty acids (SCFAs), LPS, etc. Some probiotic from intestinal microorganism, such as Bifidobacterium (Shakib, Shahraki, Razavi, & Hosseinzadeh, 2019), Alloprevotella, and Lactobacillus, have closely related with the moderation of MetS.…”
mentioning
confidence: 99%